2017
DOI: 10.1038/srep42198
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Methylation and its Relationship to Abundance and Diversity of arsM Genes in Composting Manure

Abstract: Although methylation is regarded as one of the main detoxification pathways for arsenic (As), current knowledge about this process during manure composting remains limited. In this study, two pilot-scale compost piles were established to treat manure contaminated with As. An overall accumulation of methylated As occurred during 60 day-composting time. The concentration of monomethylarsonic acid (MMA) increased from 6 to 190 μg kg−1 within 15 days and decreased to 35 μg kg−1 at the end of the maturing phase; wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Assessments of As methylation in soils and other environments have been hindered partly by limited databases for taxonomic classification. 20,21,49 The more extensive 726 protein sequence database developed for this study, along with a primer pair having greater degeneracy to amplify a broad range of arsM sequences, has enabled a deeper examination of arsM phylogenetic diversity. This study demonstrates the utility of these new tools, in conjunction with analyses of physiological responses to As, in probing relationships between community structure and biomethylation function.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Assessments of As methylation in soils and other environments have been hindered partly by limited databases for taxonomic classification. 20,21,49 The more extensive 726 protein sequence database developed for this study, along with a primer pair having greater degeneracy to amplify a broad range of arsM sequences, has enabled a deeper examination of arsM phylogenetic diversity. This study demonstrates the utility of these new tools, in conjunction with analyses of physiological responses to As, in probing relationships between community structure and biomethylation function.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…As-methylating bacteria widely exist in As-contaminated paddy soils and rice rhizosphere ( Jia et al, 2013 ; Zhao et al, 2013 ; Zhang S.Y. et al, 2015 ; Reid et al, 2017 ), activated sludges ( Cai et al, 2013 ), contaminated aquatic ecosystems ( Desoeuvre et al, 2016 ), copper mine ( Xiao et al, 2016 ), composting manure ( Zhai et al, 2017 ), and estuarine wetland ( Zhang et al, 2017 ). It was found that there is a significant correlation between arsC and arsM genes in the paddy soils; this suggests that the two genes coexist well in the microbial As resistance system ( Zhang S.Y.…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic is biomethylated during composting of animal manures, which often contain elevated levels of As due to the use of As-containing additives to animal feed (Yang et al, 2017;Zhai et al, 2017). However, little is known about the nature of microbes involved in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic speciation analysis of manure composts showed considerable amounts of methylated As species, especially dimethylarsenate (DMAs[V]) (Yang et al, 2017). DMAs(V) and, to a less extent, methylarsenate (MAs[V]), were formed during composting of manures, with the formation of methylated arsenicals being correlated with the copy number of microbial arsM genes (Zhai et al, 2017). It therefore appears that As biomethylation is an important process of As transformation during the composting process of animal manures.…”
Section: Introductionmentioning
confidence: 99%